Interactions Between Dyspnea and the Brain Processing of Nociceptive Stimuli: Experimental Air Hunger Attenuates Laser-Evoked Brain Potentials in Humans - Dangers, Laurence; Laviolette, Louis; Similowski, Thomas; Morélot-Panzini, Capucine (Frontiers in Physiology, 2015)
Dyspnea and pain share several characteristics and certain neural networks and interact with each other. Dyspnea-pain counter-irritation consists of attenuation of preexisting pain by intercurrent dyspnea and has been shown to have neurophysiological correlates in the form of inhibition of the nociceptive spinal reflex RIII and laser-evoked potentials (LEPs). Experimentally induced exertional dyspnea inhibits RIII and LEPs, while "air hunger" dyspnea does not inhibit RIII despite its documented analgesic effects. We hypothesized that air hunger may act centrally and inhibit LEPs. LEPs were obtained in 12 healthy volunteers (age: 21-29) during spontaneous breathing (FB), ventilator-controlled breathing (VC) tailored to FB, after inducing air hunger by increasing the inspired fraction of carbon dioxide -FiCO2- (VCCO2), and during ventilator-controlled breathing recovery (VCR). VCCO2 induced intense dyspnea (visual analogue scale = 63% ± 6% of full scale, p<0.001 vs. VC), predominantly of the air hunger type. VC alone reduced the amplitude of the N2-P2 component of LEPs (∆ = 24.0% ± 21.1%, p<0.05, effect-size = 0.74) predominantly through a reduction in P2, and the amplitude of this inhibition was further reduced by inducting air hunger (∆ = 22.6% ± 17.9%, p<0.05, effect-size = 0.53), predominantly through a reduction in N2. Somatosensory-evoked potentials (SEPs) were not affected by VC or VCCO2, suggesting that the observed effects are specific to pain transmission. We conclude that air hunger interferes with the cortical mechanisms responsible for the cortical response to painful laser skin stimulation, which provides a neurophysiological substrate to the central nature of its otherwise documented analgesic effects.